2022
DOI: 10.9758/cpn.2022.20.2.320
|View full text |Cite
|
Sign up to set email alerts
|

Association between Attention Deficit Hyperactivity Disorder Medication and Depression: A 10-year Follow-up Self-controlled Case Study

Abstract: Objective There is clinical concern that the stimulant methylphenidate (MPH) might increase the risk of depression, particularly in children. This study aimed to investigate the association between MPH use and the risk of depression. Methods A population-based electronic medical records database was used. We obtained claims data for prescription of ADHD medication, diagnosis of depression, and prescription of antidepressant medication between January 2007 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Children with ADHD have high rates of depression and anxiety (25−41%) [74][75][76]. Recently, Oh et al [77] also showed a temporal connection between depression and MPH use in adolescents with ADHD. Therefore, the association between LDAEP and ADHD can also be interpreted in terms of emotional comorbidities [43,70,78].…”
Section: Discussionmentioning
confidence: 99%
“…Children with ADHD have high rates of depression and anxiety (25−41%) [74][75][76]. Recently, Oh et al [77] also showed a temporal connection between depression and MPH use in adolescents with ADHD. Therefore, the association between LDAEP and ADHD can also be interpreted in terms of emotional comorbidities [43,70,78].…”
Section: Discussionmentioning
confidence: 99%
“…Rearing LHRs with many conspeci cs did not signi cantly ameliorate ADHD-like behaviors, suggesting that stimulation from the environment is more effective in improving ADHD-like behavior than stimulation from interaction with many children of the same age. Although medications are the rst line treatment for ADHD [52], the most prevalent psychostimulant methylphenidate may give negative impact physically and mentally [53][54][55]. Taken such risks of pharmacological interventions, it may be necessary to become more proactive in nurturing ADHD children in an EE.…”
Section: Discussionmentioning
confidence: 99%
“…Rearing LHRs with many conspecifics did not significantly ameliorate ADHD-like behaviors, suggesting that stimulation from the environment is more effective in improving ADHD-like behavior than stimulation from interaction with many children of the same age. Although medications are the first-line treatment for ADHD [ 63 ], the most prevalent psychostimulant methylphenidate may have negative impacts physically and mentally [ 64 , 65 , 66 ]. With such risks of pharmacological interventions, it may be necessary to become more proactive in nurturing ADHD children in an EE.…”
Section: Discussionmentioning
confidence: 99%